FAKTOR RISIKO KEJADIAN KARIES GIGI PADA ORANG DEWASA USIA 20-39 TAHUN DI KELURAHAN DADAPSARI, KECAMATAN SEMARANG UTARA, KOTA SEMARANG - Ziyaan Azdzahiy Bebe; Henry Setyawan Susanto; Martini Martini (Jurnal Kesehatan Masyarakat (Undip), 2018)
Caries is a disease of dental hard tissue, enamel, dentine and cementum, caused by the activity of microorganism in carbohydrate that can be fermented. Based on data from DKK Semarang in 2014-2016, the highest dental caries prevalence belong to 20-44 age group. Calculus incidence reached largest increase and continue at the age 30 years and increases by age. The population in this study is 138 with sample size 103.The purpose of this study is to analyze risk factors of dental caries among adults 20-39 years old. The type of research is analytic observational with cross sectional study design. Dependent variable is dental caries and independent variables are oral hygiene, teeth, pH saliva, score, component of glucose consumption, and toothbrushing practice. Collecting data with index (plaque, oral hygiene, pH saliva), observation, and interview. Data analysis using chi square test. The result of bivariate analysis showed that teeth (p=0.016, POR=5.6), pH saliva (p= 0.015, POR=4.0), plaque (p= 0.038, POR=3.4), and consumption component glucose (p=0.011, POR=7.1) are a risk factor . While, oral hygiene (p = 0.078, POR= 3.3) and tooth brushing practice (p = 0.684, POR = 2.3) are not a risk factor for dental caries. It is recommended adults do the correct steps of tooth brushing (movement of toothbrushes rotating and up-down positioning 45°, duration 2-3 minutes, eight-fold per-septan, and brushing teeth after consumpt glucose), toothbrush <15 minutes after eating, and consumpt cariostatic and anticariogenic foods.